IMPROVING THE EXISTING SYSTEM OF HUI FINANCING - A. N. Ryahovskaya; O. G. Kryukova; E. A. Arsenova (Стратегические решения и риск-менеджмент)
HUI reforming should provide improvement in the procedure of control, accounting and applying funds from the city budget for building maintenance and repair, as well as for organization and redirection of cash flows. The article discusses possible financing resources: main, additional, consolidated. Directions for improving system of forming HUI financial resources are suggested. Building this sector financing system requires integration of efforts and concerted operation of the authorities, financial institutes, organizations of various patterns of ownership and private individuals.